Kebebasan Beragama dalam Perspektif al-Qur’an - Kartika Nur Utami (Kalimah: Jurnal Studi Agama dan Pemikiran Islam, 2018)
Freedom in choosing beliefs is the right of all human beings. Even Human Rights has been mentioned about basic human rights in detail, which one of them is freedom of the ‎interest and religion. The detail is also practiced in Indonesia According to 1945 Constitution (UUD) of Republic of Indonesia, it is said that the state guarantees the freedom for the ‎people to embrace the religion of their choice. Likewise with Islam, it also regulates ‎freedom of religion as mentioned in the QS. al-Baqarah. [2] 256. Unfortunately, ‎although there are numbers of literatures saying that the freedom of choosing religion is ‎a human right, there is still a compulsion in choosing religion in various ways. This paper ‎will focus on how freedom of choosing a religion based on the principles of la> ‎Ikra>ha fi> al-Di>n contained in the QS. al-Baqarah. [2] 256. By studying from various ‎tafsir, the author concludes later that the concept of la> ‎Ikra>ha fi> al-Di>n in that ‎verse explains the freedom for a man in choosing a religion, whether he wants to choose ‎Islam or non-Islam. This freedom, however, is organized after becoming a Muslim, in accordance with the practice of Shari'a of Islam in kaffah. It means that ‎the choice to be a Muslim is a genuine experience and embraces huge consequences. In addition, this verse shows how much Islam respects for freedom in ‎embracing any religion and belief. It is a warning for Muslims not to force other people ‎to embrace Islam because it is the preference of sincerity of a person who comes from ‎his own heart without any coercion.‎